2021
DOI: 10.1128/msphere.00977-20
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Bioinformatic Assessments of the Variability of Neisseria gonorrhoeae Vaccine Candidates

Abstract: A protective vaccine is the only viable way to stop the spread of gonorrhea in the face of rising antibiotic resistance. However, the notorious phase and antigenic variation of Neisseria gonorrhoeae surface proteins remains one of the challenges in vaccine development. To facilitate vaccine advancement efforts, we carried out comprehensive bioinformatic analyses of sequence variation by comparing 34 gonorrhea antigen candidates among >5,000 clinical N. gonorrhoeae isolates deposited in the Neisseria PubMLST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…MafA and PilE were excluded from the in silico analysis as these are known to be very heterogenic antigens in Neisseria spp. due to frequent intrachromosomal recombination 43,44 . The mean and the range of amino acid identity of the 28 proteins with respect to NZ98/254 are indicated in Table 2.…”
Section: Omv Antigen Selection Sequence Conservation and Expressionmentioning
confidence: 99%
“…MafA and PilE were excluded from the in silico analysis as these are known to be very heterogenic antigens in Neisseria spp. due to frequent intrachromosomal recombination 43,44 . The mean and the range of amino acid identity of the 28 proteins with respect to NZ98/254 are indicated in Table 2.…”
Section: Omv Antigen Selection Sequence Conservation and Expressionmentioning
confidence: 99%
“…one can find the gonococcal genetic island in N. meningitidis , capsule biosynthesis ( cps ) loci in some commensal Neisseria ; similarly, iron transport systems like FetB or TbpB or adhesion structures such as type IV pili are present in both pathogenic Neisseria and commensals [56–59].…”
Section: Gonococcal Virulence Factors Are Diverse Which May Influence...mentioning
confidence: 99%
“…For example, several studies have shown that many virulence determinants are shared between both pathogenic Neisseria species and commensals; e.g. one can find the gonococcal genetic island in N. meningitidis, capsule biosynthesis (cps) loci in some commensal Neisseria; similarly, iron transport systems like FetB or TbpB or adhesion structures such as type IV pili are present in both pathogenic Neisseria and commensals [56][57][58][59].…”
Section: Gonococcal Virulence Factors Are Diverse Which May Influence...mentioning
confidence: 99%
“…In closing, we highly encourage the Neisseria research community to support and focus on increasing the collection of commensal Neisseria by both clinical and academic laboratory groups, and sequence these isolates to broaden the database of genomic data for commensal Neisseria species. Not only will these isolates and corresponding sequence data sets aid in the fight against resistance by characterizing Neisseria alleles available for intragenus transfer, they may also aid the Neisseria research community by providing a pool of data to study other common/divergent genomic features and Neisseria biology at large, such as the presence and importance of prophages ( 160 ), the diversity of anti-phage defense systems ( 161 ), the identification of toxin/antitoxin systems ( 146 ), patterns of killing through DNA methylation ( 83 ), and identifying immunogenic antigens as candidate vaccines ( 162 ).…”
Section: Canary In the Coal Mine: The Benefits Of Surveillance In Com...mentioning
confidence: 99%